Prevalence of acute kidney injury in Mexico; a systematic review and meta-analysis of pre-pandemic reports - Jose J. Zaragoza; Jonathan S. Chavez-Iñiguez; Armando Vazquez-Rangel (Renal Failure)
Background Acute Kidney Injury (AKI) is a health problem worldwide, accounting for high hospital morbidity and mortality. There is little available information regarding the characteristics and incidence of AKI in Latin America (LA), especially in Mexico.Objectives Systematically search the literature and perform a meta-analysis of the epidemiology of AKI in Mexico, to provide data on AKI and kidney replacement therapy (KRT) that would contribute to general knowledge in this matter.Methods We performed a systematic search for articles in pediatric and adult patients admitted to the general ward, Emergency Room or Intensive Care Unit published between January 1, 2000, and September 30, 2024. MEDLINE LILIACS, EMBASE and SciELO were searched, as additional reports from supplements, abstracts, and conference sessions. We performed a random-effects meta-analysis for clinically and methodologically comparable studies to estimate the frequency of AKI and KRT. We calculated pooled estimates stratified by age group, year of publication, and setting.Results 83 full-text articles were included. The percentage of AKI was calculated at 35% (95% CI, 28–42). Mortality for AKI adult patients was 36% (95% CI, 28–45). An overall KRT rate was 7% (95% CI, 6–9), all-cause mortality for AKI requiring KRT was 49% (95% CI, 42–56), with a global Ι2 estimated in 99.87% (p < 0.01).Conclusion AKI is common in Mexico and remains a main public health problem that needs to be addressed at every level of care. Efforts should be made to reinitiate AKI research and control in Mexico and LA.